2020
DOI: 10.6065/apem.1938144.072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term growth hormone therapy in a girl with Floating-Harbor syndrome

Abstract: Floating-Harbor syndrome is a rare autosomal dominant disorder that presents with short stature, facial dysmorphism, significantly delayed bone age, skeletal abnormalities, speech and language problems, and intellectual disabilities. Although short stature is one of the main clinical manifestations, use of growth hormone therapy in Floating-Harbor syndrome patients has been limited. Only a few reports have investigated the response to growth hormone therapy with regard to final adult height. We report the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
1
6
0
2
Order By: Relevance
“…It has been hypothesized that FHS phenotype is caused by defects in signaling downstream of IGF-1 and not by a decrease in either GH or IGF-1 secretion and/or activity itself. This hypothesis is supported by previous studies that showed limited GH efficacy in FHS ( Son et al (2020) ).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…It has been hypothesized that FHS phenotype is caused by defects in signaling downstream of IGF-1 and not by a decrease in either GH or IGF-1 secretion and/or activity itself. This hypothesis is supported by previous studies that showed limited GH efficacy in FHS ( Son et al (2020) ).…”
Section: Discussionsupporting
confidence: 86%
“…We have systematically reviewed all published studies describing the spectrum of identified mutations in FHS patients. These studies include patients from various countries, including the United States ( Homma et al (2019) ), China ( Zhang et al (2019) ), South Korea ( Son et al (2020) ) Japan ( Nagasaki et al (2014) ), and others. The results of this analysis are presented in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations